Understanding and Managing Stress in the New Era of Global Economic Conditions - Shatnataphat, Chattawat (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2025)
This research aimed to: 1) explore the role of the new global economy, 2) analyze the understanding and management of stress in the context of the new global economy, and 3) identify tools to aid in understanding and managing stress in the new global economic context. It employed qualitative research methods, analyzing documents to highlight relevant issues with credibility and quality in managing stress within the economic context. The findings revealed that: 1) Changes in knowledge creation play a crucial role in preparing for economic adaptation, leading to both new opportunities and concerns. Adaptation to technological changes results in instability and increased competition in the labor market, necessitating consideration of both positive and negative impacts to develop suitable policies and activities for rapidly changing economic situations. 2) Understanding and managing stress in the new global economic era involve multiple factors affecting individual and organizational adaptation, driven by technological and economic changes leading to income and job insecurity, necessitating organizational adjustments. This study is significant for policy development and management guidelines to cope with uncertainty and appropriate changes in the future, and 3) Managing stress in the new global economic situation should utilize analytical tools such as economic data analysis software and qualitative and quantitative research, with social technology aiding in data dissemination, to enhance coping abilities and foster positive mental states in the challenging economic circumstances of today’s world.